A Review of Rangeland Privatisation and its Implications in the Tibetan Plateau, China. (1st January 2005) - Zhaoli, Yan; Ning, Wu; Dorji, Yeshi; Jia, Ru
Abstract : The Tibetan plateau of China is one of the world's major pastoral areas, in which rangeland management underwent fundamental changes in the twentieth century. This article reviews the rangeland privatisation process in the Tibetan plateau over the last ten years, examining cases from Hongyuan, Zoige and Maqu Counties in the eastern part of the plateau, Nyima County in the northwestern part and Dingri County in the southwestern part.Rangelands have been allocated to individual households or 'the least contracting unit' starting from 1996, but the process of rangeland privatisation was diverse and is still ongoing in the western part of the Tibetan plateau.Rangeland privatisation has some significant impacts on local people and their environment. First, many rangelands are inequitably allocated due to their highly variable topography, productivity and availability of water resources. Secondly, access to social and economic services has been made more difficult for some, while social conflicts have increased. Thirdly, privatisation of rangeland and sedentarisation of nomads needs matching infrastructure but that is still missing in many places. Meanwhile, privatisation of rangeland has led to increased labour inputs in some places and added more workload onto women and children.The article concludes that rangeland privatisation was intended to stop further rangeland degradation and to provide nomads with better lives. However, more study is needed on managing rangeland in an appropriate way.